Sell It on eBay, Second Edition : a Guide to Successful Online Auctions - Malina, Toby; Heid, Jim (Peachpit Press, 2005)
EBay can mean big business, but only if you know how to use the auction site effectively. To ensure that your wares don't just sell, but sell quickly, at the desired price, and without any complications in shipping or payment, you need this no-nonsense guide. This artfully designed book by eBay aficionados Jim Heid and Toby Malina delivers the lowdown on selling on eBay. Toby and Jim's clear, authoritative text is augmented by the book's appealing and helpful graphics. They show you how to take flattering photos of your items and present them in attractive, effective eBay pages. The guide also includes up-to-date coverage of all that's new and improved on eBay-from My eBay 2.0 to PayPal Buyer Credit, advanced search functionality, the Shipping Center, eBay Accounting Assistant, and more. Filled with need-to-know information about everything from payment methods to shipping considerations and establishing starting bid prices, this entertaining and practical guide is an essential stop on the road to eBay success.